2021
DOI: 10.1155/2021/6669742
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasite Infections and Their Associated Factors among Food Handlers Working in Selected Catering Establishments from Bule Hora, Ethiopia

Abstract: Intestinal parasites are responsible for one of the major health problems like food contamination with socioeconomic effects in the world with a prevalence rate of 30-60%, in developing countries that lie within tropical and subtropical areas. They pose a reasonable public health burden, particularly in low- and middle-income countries, including Ethiopia. Globally, due to intestinal parasitic infections, around 3.5 billion people are affected and more than 200,000 deaths are reported annually. Around 50000 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 35 publications
2
41
1
Order By: Relevance
“…The study found that 41.6% (95% CI 36.6% to 46.4%) of food handlers had one or more intestinal parasites. The prevalence of intestinal parasites reported in this study was comparable with findings of studies conducted among food handlers in Bule Hora (46.3%) 16 and Addis Ababa University (45.3%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The study found that 41.6% (95% CI 36.6% to 46.4%) of food handlers had one or more intestinal parasites. The prevalence of intestinal parasites reported in this study was comparable with findings of studies conducted among food handlers in Bule Hora (46.3%) 16 and Addis Ababa University (45.3%).…”
Section: Discussionsupporting
confidence: 88%
“…For instance, a systematic review and meta-analysis reported that the overall pooled prevalence estimate of intestinal parasites among food handlers in food service establishments in Ethiopia was 33.6% (95% CI 27.6% to 39.6%), 13 and the common factors associated with high prevalence of intestinal pathogens among them are poor hand hygiene, inadequate access to water and sanitation facilities, and poor socioeconomic conditions. [13][14][15][16][17][18] However, the prevalence and risk factors may be different across various settings. Accordingly, this study was conducted to assess the prevalence of intestinal parasites and the associated factors among food handlers working in food establishments in the Lideta subcity of Addis Ababa, Ethiopia.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…However, the present finding's prevalence reports are lower than that from other African countries such as 65% in Gabon [ 29 ], 49.6% in Ghana [ 30 ], and 76.2% in Kenya [ 27 ]. Differences in findings among various studies can be explained by variations in geography, socioeconomic conditions, difference in parasitological examination methods, the number of study population, and the level of awareness about the transmission of IPIs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, it is estimated that infections caused by intestinal parasites affect 3.5 billion people, 450 million of whom are symptomatic and have health problems as a direct result of the disease. Nematodes are largely responsible for these diseases, including Ascaris lumbricoides , Trichiuris trichiuria , Ancylostoma duodenale and Strongyloides stercoralis [ 1 , 2 , 3 , 4 , 5 , 6 ]. Diseases caused by intestinal nematodes can cause, among others, abdominal pain, dehydration, weight loss, anemia, intestinal obstruction, disorders of mental and physical development, malabsorption, inflammation and in severe cases, if left untreated, these can even lead to death [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%